A randomized trial evaluating the effects of change in dairy food consumption on cardio-metabolic risk factors. (29th August 2020) - Benatar, Jocelyne R; Jones, Emma; White, Harvey; Stewart, Ralph AH
Abstract: Background: It is currently not known whether dairy food influences the risk of cardiovascular disease or diabetes. This study evaluates effects of changing dairy intake on cardio-metabolic risk factors. Methods: 180 healthy volunteers were randomised to increase, reduce or not change their dairy intake for 1 month in response to dietary advice. Body weight, waist circumference, blood pressure, fasting plasma lipids, insulin resistance and C-reactive protein (CRP) were measured at baseline and after 1 month and compared by dietary group. Results: 176 (98%) subjects completed the study. Average change in self-reported dairy fat intake for increased dairy food was +0.9 SD 1.1 g/day (+71%), no change was −2.1 SD 0.4 g/day (−15%) and decreased dairy food was −10.8 SD 1.2 g/day (−77%) respectively. There was no statistically significant change in LDL or HDL cholesterol, triglycerides, systolic or diastolic blood pressure, C-reactive protein, glucose or insulin with 95% CI standard mean differences <0.2 for all and CRP <0.3. There was a small increase in weight (+0.4 kg, SD 3.1) in those asked to increase dairy food. Conclusions: In healthy volunteers, dietary advice to change dairy intake for 1 month did not have a clinically significant effect on cardio-metabolic risk factors. These observations suggest that dairy food can be included as part of a normal healthy diet without increasing cardio-metabolic risk. Trial registration number: ACTRN12612000574842